2007
DOI: 10.1016/j.jcf.2006.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Achromobacter xylosoxidans in cystic fibrosis: Prevalence and clinical relevance

Abstract: The prevalence of A. xylosoxidans infection or colonisation is probably underestimated. Colonised patients are mostly older, with more pronounced lung damage and lower lung function values. Although there was more need for intravenous antibiotic treatment courses, no faster decline in lung function was observed in A. xylosoxidans positive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
139
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(160 citation statements)
references
References 10 publications
15
139
1
5
Order By: Relevance
“…The cumulative prevalence of Achromobacter isolation of 11% in our center is comparable to those previously reported for small centers, which ranged from 5 to 29% (11,12), although this spans 3 decades, making the incidence of infection very low. While others have reported that older patients and patients with greater lung disease burden appear to be predisposed to infection with Achromobacter species (11, 18), we did not observe any correlation between age, nutritional status, CF comorbidities, baseline lung status, or home oxygen use and incident infection.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The cumulative prevalence of Achromobacter isolation of 11% in our center is comparable to those previously reported for small centers, which ranged from 5 to 29% (11,12), although this spans 3 decades, making the incidence of infection very low. While others have reported that older patients and patients with greater lung disease burden appear to be predisposed to infection with Achromobacter species (11, 18), we did not observe any correlation between age, nutritional status, CF comorbidities, baseline lung status, or home oxygen use and incident infection.…”
Section: Discussionsupporting
confidence: 86%
“…Studies have attributed persistent Achromobacter infections predominantly to A. xylosoxidans (2,11,12,18), with a few exceptions, including A. insuavis and A. dolens (5,6). We now know that this may represent a broader species distribution.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Decline in lung function was assessed using the variable annual percentage loss of FEV 1 . Informed consent for compassionate use was obtained from all individual participants.…”
Section: Methodsmentioning
confidence: 99%
“…Achromobacter xylosoxidans is a gram-negative non-fermentative rod that is increasingly cultured in sputum from adult cystic fibrosis (CF) patients with moderate to severe lung compromise [1,2]. Its clinical implications are still to be determined [3] and therefore there is limited evidence on specific treatment.…”
Section: Introductionmentioning
confidence: 99%